The Rise and Fall of Brazilian Inequality : 1981-2004 - Ferreira, Francisco H.G.; Leite, Phillippe G.; Litchfield, Julie A. (World Bank, Washington, DC, 2012)
Measured by the Gini coefficient, income inequality in Brazil rose from 0.57 in 1981 to 0.63 in 1989, before falling back to 0.56 in 2004. This latest figure would lower Brazil's world inequality rank from 2nd (in 1989) to 10th (in 2004). Poverty incidence also followed an inverted U-curve over the past quarter century, rising from 0.30 in 1981 to 0.33 in 1993, before falling to 0.22 in 2004. Using standard decomposition techniques, this paper presents a preliminary investigation of the determinants of Brazil's distributional reversal over this period. The rise in inequality in the 1980s appears to have been driven by increases in the educational attainment of the population in a context of convex returns, and by high and accelerating inflation. While the secular decline in inequality, which began in 1993, is associated with declining inflation, it also appears to have been driven by four structural and policy changes which have so far not attracted sufficient attention in the literature, namely sharp declines in the returns to education; pronounced rural-urban convergence; increases in social assistance transfers targeted to the poor; and a possible decline in racial inequality. Although poverty dynamics since the Real Plan of 1994 have been driven primarily by economic growth, the decline in inequality has also made a substantial contribution to poverty reduction.